Horizons Community Board collection: antimicrobial materials and surfaces. Issue 6 (25th May 2022) - Insua, Ignacio; Martín-Fabiani, Ignacio
Abstract : A themed collection on antimicrobial materials and surfaces, guest edited by Materials Horizons and Nanoscale Horizons Community Board members Ignacio Martín-Fabiani and Ignacio Insua.